Mealybugs (Hemiptera: Coccomorpha: Pseudococcidae) with oral rim ducts; description of a new genus and species from Turkey, and discussion of their higher classification within the Pseudococcidae - Kaydan, Mehmet Bora; Szita, Éva (Zootaxa, 2017)
A new monotypic mealybug genus with oral rim ducts, Bromusicoccus Kaydan gen. n. (Hemiptera: Pseudococcidae: Pseudococcinae), is described from Turkey. The higher classification of mealybug genera with oral rim tubular ducts worldwide is discussed and a key is provided to separate them.